Phenolics in Primula veris L. and P. elatior (L.) Hill Raw Materials - Katarzyna Bączek; Jarosław L. Przybył; Małgorzata Mirgos; Olga Kosakowska; Izabela Szymborska-Sandhu; Zenon Węglarz (International Journal of Analytical Chemistry)
Primula veris L. and Primula elatior (L.) Hill represent medicinal plants used for the production of herbal teas and preparations with antioxidant and expectorant activity. Flowers and roots of both species possess the same biological activity. In the presented study, raw materials of wild growing P. veris and P. elatior were compared in terms of the content and composition of phenolic compounds using a fast and simple HPLC-DAD method. The study showed that flowers of both species were rich in flavonoids. However, P. veris flowers were characterized with a distinctly higher content of isorhamnetin-3-O-glucoside, astragalin, and (+)-catechin, whereas P. elatior occurred to be a richer source of rutoside and isorhamnetin-3-O-rutinoside. Hyperoside was found exclusively in P. elatior flowers. Phenolic glycosides (primverin and primulaverin) were identified only in the roots. Their content was about ten times higher in P. veris in comparison with P. elatior underground organs. The obtained results clearly show that both Primula species differ distinctly in terms of the content and composition of phenolic compounds. The compounds differentiating both species to the highest degree (hyperoside, in flowers, as well as primverin and primulaverin, in the roots) may be useful chemical markers in the identification and evaluation of both species.